Editorial - Shelja Sen (International Journal of Narrative Therapy and Community Work, 2024)
Shelja Sen is narrative therapist, writer and co-founder of Children First, New Delhi. Her latest book is Reclaim Your Life and she is also a columnist with a national newspaper, Indian Express. Shelja has worked as a narrative practitioner and teacher for over 20 years in various contexts in the UK and India. She is an international faculty member at Dulwich Centre Foundation, Adelaide, and a clinical tutor at The University of Melbourne, Australia. Shelja is a curator of the unique skills, expertise and know-how of the children, young people and families she has the honour of working with, and is committed to building innovative, culturally aligned, ethical practices using a feminist intersectional lens.